HUBUNGAN KINERJA PUSKESMAS DENGAN BESARNYA ANGGARAN PUSKESMAS DI KABUPATEN KETAPANG - B61110059, SYAIFUL AKHYAR (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT In 2004 there was a change in managing and planning budget in Ketapang regency where previously the budget was managed and planned by HealtzehdÂ Departemen but later it was handled by Health Centre (Puskesmas) but it did not run well until it was taken over by Health Departemen in 2010. Bottom up preparation and decentralized management are expected to region condition to achieve better result. The purpose of the research was to find out the correlation of Centre Health work with Health Centre budget in managing and using the budget before and after the change of budget planning and to investigate the Health Centre program. The research is a descriptive cas study. The data was collected by analysing document. Data was analysed by calculating time series to describe patterns of utilizing budget and Health Centre programs between 2006 and 2008. Health Centre budget management is according to Ministry of Home Affairs decree No 29 Year 2002. Based on the way financial record and types of report from the treasurer, it showed that there was no difference between managing and using the budget before and after the change of budget system. After the change, there was a rise in budget for 6 major Health Centre program.However, environmental health program fell to 0% in 2005 budget. Before the policy changed in 2003, Health Centre budget was mostly from DASK Health Centre (40,84%). After the changes in policy, the budget was from DASK Health Departmentwith 50,09% in 2004 and 30,46% in 2005.Health Centre budget allocation seemed fairly bad if seen from over Costing SPM, while the rest was below Costing SPM. The realisation of 60 % program budget from Health Centre tended to be smaller if managed by Health Centre than it was managed by Health Department. After policy change,more than half indicators (51,43%) of Health Clinic work in Ketapang regency went stable, while 34,41% work fell down. The change of policy in planning and managing the budget of Health Centre in Ketapang district did improve the Health Clinic workÂ